Output Commercialization as Three-Way Traffic for Sugarcane Farming Households in Kwara State of Nigeria - M.S, Sadiq; I.P, Singh; M, Lawal; P.B, Yisa (American International Journal of Multidisciplinary Scientific Research, 2018)
The study empirically determined the factors that influenced household sugarcane output commercialization in Kwara State of Nigeria using undated data elicited via structured questionnaires complemented with interview schedule from 105 active sugarcane farmers chosen through multi-stage sampling design during the 2017 production season. The collected data were analyzed using both descriptive and inferential statistics. The empirical findings showed poor extension services, inadequate credit facilities, failure of the farmers to utilize their social capital, lack of scientific storage facilities and health-related issues to be the major factors that affected sugarcane output commercialization the studied area. Therefore, the study recommended that the farmers in the studied area should be advised to pool their social capital together in order to become economically viable thereby maximizing the pecuniary economic advantages of sugarcane value chain in the studied area.